ANALISIS STEM (SCIENCE, TECHNOLOGY, ENGENERING, AND MATHEMATICSS) MATERI KELISTRIKAN PADA BUKU TEMATIK TEMA 3 KELAS 6 SEKOLAH DASAR - Yuanita Yuanita; Feni Kurnia (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
This research is motivated by the importance of combining STEM to answer problems in daily life by utilizing current technological advances that can be applied in learning. One of which is in science learning, including Science, Technology, and Designing skills and arrange it systematically and logically (Mathematics). This study aims to analyze STEM contained in the theme 3 in thematic book 3 of the sixth grade in elementary school. Data collection techniques in the form of the latest edition of the teacher and student thematic book documentation in accordance with Minister of Education and Culture of the Republic of Indonesia Number 37 of 2018. Based on the results of STEM analysis on theme 3 with sub theme 1 titled Inventors that Changes the World, it can be found out that there are components of Science, Technology and Engineering. On sub-theme 2 about the Discovery and Its Benefits, it is found out that  there are components of Science and Engernering, and on sub-theme 3 about Let's Become an Inventor there are components of Science and Mathematics. Based on this, in the IPA thematic book the electrical material for theme 3 of class VI elementary school in each sub-theme is incomplete in combining the components of Science, Technology, Engineering and Mathematic (STEM) in one theme. Keywords: STEM, Thematic Books, Electricity